OP19 Content analysis of advance directives completed by patients as part of advance care planning: insights gained from the ACTION trial. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Zwakman, M; van Delden, JJM; Caswell, G; Christensen, CA; Deliens, L; Ingravallo, F; Jabbarian, LJ; Johnsen, AT; Korfage, IJ; Mimic, A; Preston, NJ; Kars, MC
Abstract : Background: Writing an Advance Directive (AD) is often seen as a part of Advance Care Planning (ACP). ADs may include specific preferences regarding future care and treatment and information that provides a context for healthcare professionals and relatives in case they have to make decisions for the patient. The aim of this study was to get insight into the content of ADs as completed by patients with advanced cancer who participated in ACP conversations. Methods: A content analysis and descriptive statistics were conducted to describe the content of the completed My Preferences forms, an AD used in the intervention arm of the ACTION trial, testing the effectiveness of the ACTION Respecting Choices ACP intervention. Results: In total, 33% of 439 patients who received the ACTION RC ACP intervention completed a My Preferences form. Document completion varied per country: 9.6% (United Kingdom), 21% (Denmark), 27.6% (Belgium), 43.8% (the Netherlands), 61.3% (Italy) and 64.3% (Slovenia). Content analysis showed that 'maintaining normal life' and 'experiencing meaningful relationships' were important for patients to live well. Fears and worries mainly concerned disease progression, pain or becoming dependent. Patients hoped for prolongation of life and to be looked after by healthcare professionals. Most patients preferred to be resuscitated and 44% of the patients expressed maximizing comfort as their goal of future care. Most patients preferred 'home' as final place of care. Conclusions: My Preferences forms provide some insights into patients' perspectives and preferences. However, understanding the reasoning behind preferences requires conversations with patients.